Regional citrate versus systemic heparin anticoagulation for continuous renal replacement in critically ill patients - Kutsogiannis, Demetrios J.; Gibney, R.T.Noel; Stollery, Daniel; Gao, Jun (Kidney international, 2005)
Regional citrate versus systemic heparin anticoagulation for continuous renal replacement in critically ill patients. We determined the effect of regional citrate versus systemic heparin anticoagulation for continuous renal replacement therapy in critically ill subjects suffering from acute renal failure who were not at high risk for hemorrhagic complications. Between April 1999 and June 2002, 30 critically ill subjects requiring continuous renal replacement therapy and using 79 hemofilters were randomly assigned to receive regional citrate or systemic heparin anticoagulation. The median hemofilter survival time was 124.5 hours (95% CI 95.3 to 157.4) in the citrate group, which was significantly longer than the 38.3 hours (95% CI 24.8 to 61.9) in the heparin group (P < 0.001). Increasing illness severity score, male gender, and decreasing antithrombin-III levels were independent predictors of an increased relative hazard of hemofilter failure. After adjustment for illness severity, antithrombin-III levels increased significantly more over the period of study in the citrate as compared to the heparin group (P = 0.038). Moreover, after adjustment for antithrombin-III levels and illness severity score, the relative risk of hemorrhage with citrate anticoagulation was significantly lower than that with heparin (relative risk of 0.14; 95% CI 0.02 to 0.96, P = 0.05). Compared with systemic heparin anticoagulation, regional citrate anticoagulation significantly increases hemofilter survival time, and significantly decreases bleeding risk in critically ill patients suffering from acute renal failure and requiring continuous renal replacement therapy.